An Investigation of the Impact of Financial Literacy and Financial Socialization on Financial Satisfaction: Mediating Role of Financial Risk Attitude. (January 2022) - Madinga, Nkosivile Welcome; Maziriri, Eugine Tafadzwa; Chuchu, Tinashe; Magoda, Zinzi
Over the years, academics have paid a lot of attention to the topic of financial literacy. As a result, the current study investigates this topic using a unique conceptual model that was created expressly to investigate the study's claimed linkages. Three hundred eighty four people took part in the study using a web-based self-administered questionnaire. The data was analysed using Partial Least Square Structural Equation Modelling (PLS-SEM). The outcomes of this study demonstrate that those who are more willing to take chances are more likely to be content with their financial situation. Improving financial literacy and socializing has a direct impact on financial happiness. Furthermore, financial risk attitude positively facilitates the association of a customer's monetary education and gratification associated with education. In addition, financial risk attitude positively intercedes the association of financial socialization and monetary gratification. Financial satisfaction is observed to be of paramount importance for customers, company as well as the government. The findings of this article promote the successful delivery of financial services to established target groups, followed by recommendations for the provision of financial literacy for individuals. Furthermore, the outcomes of this research have led the way for the discovery of insights potentially useful for public policy development.